Anxiety, Sadness, and Emotion Specificity: The Role of Music in Consumer Emotion and Advertisement Evaluation - Septianto, Felix (ASEAN Marketing Journal, 2021)
Although music could diversely influence consumer judgment process and behavior, it is still unclear whether music can evoke discrete emotions on consumers and influence consumer evaluation toward certain advertisements. This research proposes that music could evoke sad and anxious emotion on consumers; subsequently, consumers would regulate their negative emotions in accordance to their emotion orientations: Consumers who feel sad would show high evaluation toward happy-themed advertisement, while consumers who feel anxious would show high evaluation toward calm-themed advertisement. This paper concludes with the discussion of theoretical and practical implications and conclusion of this study.